Management Information Systems for Microfinance : Catalyzing Social Innovation for Competitive Advantage. - Arvind Ashta, Bryan Barnett, Karl Dayson, Godfrey Supka (Cambridge Scholars Publishing, 2015)
Microfinance is a double bottom line sector which is growing fast, making money and doing well in a variety of socially interesting ways. The growth of its institutions requires good strategies, good control systems and informed decision-making, all of which require an appropriate Management Information System (MIS). While a good MIS is needed in any sector, the management of a double bottom line requires systems which yield information on economic, financial and social metrics. The essays in this book explore the metrics required for success in this field. Communicating on these metrics may p.